2017
DOI: 10.3390/su9101671
|View full text |Cite
|
Sign up to set email alerts
|

Stability Control of Retained Goaf-Side Gateroad under Different Roof Conditions in Deep Underground Y Type Longwall Mining

Abstract: Stability of the retained goaf-side gateroad (RGSG) is influenced mainly by the movements of the roof strata near coal seam after coalface passes by. To make effective controlling technology for the stability of the RGSG, we analyze the roof structure over the RGSG to illustrate the mechanism causing the RGSG instability under different roof conditions. We then examine the dynamic evolution of the deformation and abutment stress in the rock surrounding the RGSG during coal seam mining, using the FLAC3D numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…In recent decades, many studies have been conducted on the stability control of the RGSG. Examples of such studies can be briefly generalized as follows: design principles, high-water material [7][8][9]; the controlling methods of the stability of the RGSG packfillings, roof and sidewalls were researched in a backfilling mining system, inclined coal seam in 2010, 2011, 2013, and 2014 [10][11][12][13]; and the construction methods of the RGSG packfillings under hard roof strata, composed roof strata, and soft roof strata was studied in 2015, 2016, and 2017 [14][15][16]. The roof and sidewalls of the RGSG were maintained within acceptable limits according to the aforementioned advanced supporting theory and techniques.…”
Section: Deformations Of the Rgsgmentioning
confidence: 99%
“…In recent decades, many studies have been conducted on the stability control of the RGSG. Examples of such studies can be briefly generalized as follows: design principles, high-water material [7][8][9]; the controlling methods of the stability of the RGSG packfillings, roof and sidewalls were researched in a backfilling mining system, inclined coal seam in 2010, 2011, 2013, and 2014 [10][11][12][13]; and the construction methods of the RGSG packfillings under hard roof strata, composed roof strata, and soft roof strata was studied in 2015, 2016, and 2017 [14][15][16]. The roof and sidewalls of the RGSG were maintained within acceptable limits according to the aforementioned advanced supporting theory and techniques.…”
Section: Deformations Of the Rgsgmentioning
confidence: 99%
“…Coal pillar and no-pillar for surrounding rock control are the two mostly used layouts in longwall panel coal mining. GER is beneficial for the sustainable development of the coal mining industry by mining without the coal pillar [1][2][3][4][5] GER maintains the gob boundary roadway behind the roadway behind the working face. The original roadway is retained and used as a roadway adjacent to the working face through effective roadside backfill and road-in support technology (see Figure 1) [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Shabanimashcool and Li [24] discussed the relationship between the horizontal in-situ stress and the buckling or crushing failure of the voussoir beam structures, which provide a mechanical method for the analysis of the interaction of structures in one layer. Zhang et al [25] found that sink and rotation of the cantilever roof structure above the side of the gob generates severer pressure for the entry along the side of the gob; while the effects of this structure movement on the upper cantilever roof structure were ignored. Guo et al [26] determined the support resistance assuming that the hard roof structures play a loading role in the lower supports together; while interactional effects between the structures were ignored.…”
Section: Introductionmentioning
confidence: 99%